Eating disorders in athletes: a review of the literature - Byrne, S.; McLean, N. (Journal of Science and Medicine in Sport, 2001)
Over the last two decades an increasing amount of research has begun to examine the issue of eating disorders in athletes. While a number of studies in this area have been published, the results have not been able to clarify the nature of the relationship between athletic involvement and eating problems. This review critically evaluates existing studies of eating disorders in athletes, highlighting various methodological limitations. Studies are grouped under three main headings: uncontrolled studies; controlled studies; and studies comparing athletes with different body type requirements. A fourth section of the paper evaluates studies which have addressed the issue of gender differences in eating disorders among athletes. Suggestions are made for guidelines that will improve future research in this area.